Redox processes are major regulators of leukotriene synthesis in neutrophils exposed to bacteria Salmonella typhimurium; the way to manipulate neutrophil swarming - Golenkina, Ekaterina A.; Viryasova, Galina M.; Galkina, Svetlana I.; Kondratenko, Natalia D.; Gaponova, Tatjana V.; Romanova, Yulia M.; Lyamzaev, Konstantin G.; Chernyak, Boris V.; Sud’ina, Galina F. (Frontiers in Immunology, 2024)
Neutrophils play a primary role in protecting our body from pathogens. When confronted with invading bacteria, neutrophils begin to produce leukotriene B4, a potent chemoattractant that, in cooperation with the primary bacterial chemoattractant fMLP, stimulates the formation of swarms of neutrophils surrounding pathogens. Here we describe a complex redox regulation that either stimulates or inhibits fMLP-induced leukotriene synthesis in an experimental model of neutrophils interacting with Salmonella typhimurium. The scavenging of mitochondrial reactive oxygen species by mitochondria-targeted antioxidants MitoQ and SkQ1, as well as inhibition of their production by mitochondrial inhibitors, inhibit the synthesis of leukotrienes regardless of the cessation of oxidative phosphorylation. On the contrary, antioxidants N-acetylcysteine and sodium hydrosulfide promoting reductive shift in the reversible thiol-disulfide system stimulate the synthesis of leukotrienes. Diamide that oxidizes glutathione at high concentrations inhibits leukotriene synthesis, and the glutathione precursor S-adenosyl-L-methionine prevents this inhibition. Diamide-dependent inhibition is also prevented by diphenyleneiodonium, presumably through inhibition of NADPH oxidase and NADPH accumulation. Thus, during bacterial infection, maintaining the reduced state of glutathione in neutrophils plays a decisive role in the synthesis of leukotriene B4. Suppression of excess leukotriene synthesis is an effective strategy for treating various inflammatory pathologies. Our data suggest that the use of mitochondria-targeted antioxidants may be promising for this purpose, whereas known thiol-based antioxidants, such as N-acetylcysteine, may dangerously stimulate leukotriene synthesis by neutrophils during severe pathogenic infection.